Anaphylatoxins spark the flame in early autoimmunity - Schanzenbacher, Jovan; Köhl, Jörg; Karsten, Christian M. (Frontiers in Immunology, 2022)
The complement system (CS) is an ancient and highly conserved part of the innate immune system with important functions in immune defense. The multiple fragments bind to specific receptors on innate and adaptive immune cells, the activation of which translates the initial humoral innate immune response (IR) into cellular innate and adaptive immunity. Dysregulation of the CS has been associated with the development of several autoimmune disorders such as systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), ANCA-associated vasculitis and autoimmune bullous dermatoses (AIBD), where complement drives the inflammatory response in the effector phase. The role of the CS in autoimmunity is complex. One the one hand, complement deficiencies were identified as risk factors to develop autoimmune disorders. One the other hand, activation of complement can drive autoimmune responses. The anaphylatoxins C3a and C5a are potent mediators and regulators of inflammation during the effector phase of autoimmunity through engagement of specific anaphylatoxin receptors, i.e. C3aR, C5aR1 and C5aR2 either on or in immune cells. In addition to their role in innnate IRs, anaphylatoxins regulate humoral and cellular adaptive IRs including B cell T cell activation, differentiation and survival. They regulate B and T lymphocyte responses either directly or indirectly through the activation of anaphylatoxin receptors via dendritic cells that modulate lymphocyte function. Here, we will briefly review our current understanding of the complex roles of anaphylatoxins in the regulation of immunologic tolerance and the early events driving autoimmunity, and the implications of such regulation for therapeutic approaches that target the CS.